2016
DOI: 10.1002/cbdv.201600089
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiling of the Essential Oils of Syzygium aqueum, Syzygium samarangense and Eugenia uniflora and Their Discrimination Using Chemometric Analysis

Abstract: The essential oil compositions of the leaves of three related Myrtaceae species, namely Syzygium aqueum, Syzygium samarangense and Eugenia uniflora, were investigated using GLC/MS and GLC/FID. Altogether, 125 compounds were identified: α-Selinene (13.85%), β-caryophyllene (12.72%) and β-selinene constitute the most abundant constituents in S. aqueum. Germacrene D (21.62%) represents the major compound in S. samarangense whereas in E. uniflora, spathulenol (15.80%) represents the predominant component. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 38 publications
3
33
0
3
Order By: Relevance
“…It was also observed that most of the identified compounds are sesquiterpenes,caryophyllene for example, was often isolated in E. uniflora extraction (25,26). According to Silva (16), regardless of origin or part of E. uniflora plant used in the extraction, the sesquiterpenes show to be the main class of compounds, which corroborates the results found in this paper.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…It was also observed that most of the identified compounds are sesquiterpenes,caryophyllene for example, was often isolated in E. uniflora extraction (25,26). According to Silva (16), regardless of origin or part of E. uniflora plant used in the extraction, the sesquiterpenes show to be the main class of compounds, which corroborates the results found in this paper.…”
Section: Resultssupporting
confidence: 83%
“…Evidenced by MBC test, the essential oil tested showed bactericidal activity in the dilutions 25%, 12.5%, 6.25% and 3.125% of the bacteria tested. There are already descriptions of antimicrobial activity of E. uniflora in gram negative and gram positive bacteria, and also against yeasts (25,26,27). It is also reported, as well as in our research, the antibacterial activity of this essential oil against E. cloacae and E. aerogenes (28).…”
Section: Resultssupporting
confidence: 80%
“…Meanwhile, PCA was established by Unscrambler ® 9.7 ( CAMO SA , Oslo, Norway) after preprocessing by mean centering of the raw data of all the samples prior to the analyses. The assessments were done in triplicates for each sample …”
Section: Methodsmentioning
confidence: 99%
“…Antibacterial activity SOBEH et al (2016) showed in their study that the essential oil extracted from E. uniflora L. presented antimicrobial activity against six species of gram-positive bacteria: Staphylococcus aureus, Staphylococcus epidermidis, Bacillus licheniformis, Bacillus subtilis, Enterococcus faecalis and Staphylococcus aureus (isolated number -10442), besides three species of gram-negative bacteria (Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa) and two species of fungi (Candida parapsilosis and Candida albicans). In this study, the species B. licheniformis was the most sensitive to E. uniflora essential oil, with minimal inhibitory concentration and minimum microbicide of 0.63 mg/mL.…”
Section: Introductionmentioning
confidence: 99%